Sobre Latinoamérica - Unamuno, Miguel de, 1864-1936 (Barcelona : www.linkgua-digital.com, 2016)
A compilation of Unamuno's reflections about Latin America.
Online resource; title from ePub title page (Digitalia, viewed June 15, 2018)
Keywords: Unamuno, Miguel de, -- 1864-1936 -- Knowledge -- Latin America; Latin American literature -- History and criticism; Latin America -- Civilization; Electronic books